2017
DOI: 10.2147/ndt.s132214
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the existence of attention deficit hyperactivity disorder symptoms in children with autism spectrum disorders

Abstract: Over the years, several authors have reported symptoms of attention deficit hyperactivity disorder (ADHD) in patients with autism spectrum disorders (ASD); however, studies on the risk factors of ADHD symptoms in children with ASD are lacking. The aim of this cross-sectional study was to identify the risk factors for the development of ADHD symptoms in children with ASD. The sample consisted of 67 children with ASD who were assessed with Conner’s Parent Rating Scale-Revised (CPRS-R), and with a semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…These impaired CPT performance included higher variability in reaction time [ 24 – 26 ] as well as more omission errors and poorer sustained attention [ 27 ]. Consistent with Western research [ 13 , 15 , 18 21 , 24 – 26 ], our previous study also showed that youths with ASD had more inattentive, hyperactive/impulsive, and oppositional symptoms, and also showed worse focused attention, cognitive impulsivity, and vigilance assessed by CPT compared to age-matched TD controls [ 27 ]. A recent study used a large Finnish ASD cohort to demonstrate that siblings of probands with ASD were at risk for ADHD (5.3% in siblings vs. 1.5% in controls, adjusted relative risk 3.7), and conduct and oppositional disorders (5.0 vs. 1.9%, adjusted relative risk 2.8) [ 28 ].…”
Section: Introductionsupporting
confidence: 86%
“…These impaired CPT performance included higher variability in reaction time [ 24 – 26 ] as well as more omission errors and poorer sustained attention [ 27 ]. Consistent with Western research [ 13 , 15 , 18 21 , 24 – 26 ], our previous study also showed that youths with ASD had more inattentive, hyperactive/impulsive, and oppositional symptoms, and also showed worse focused attention, cognitive impulsivity, and vigilance assessed by CPT compared to age-matched TD controls [ 27 ]. A recent study used a large Finnish ASD cohort to demonstrate that siblings of probands with ASD were at risk for ADHD (5.3% in siblings vs. 1.5% in controls, adjusted relative risk 3.7), and conduct and oppositional disorders (5.0 vs. 1.9%, adjusted relative risk 2.8) [ 28 ].…”
Section: Introductionsupporting
confidence: 86%
“…Over the years, and lastly after the publication of DSM-5, the overlap between ASD and ADHD has been supported by an increasing number of studies (28, 3035). A recent study estimated that the prevalence of the co-occurring of ASD and ADHD is about 37–85% of children with ASD (35), supporting the hypothesis of a common neurobiological pathogenesis (35, 36). Moreover, comparing male with female, we found that ADHD with “Predominantly inattention presentation” prevails on female subgroup; while in male subgroup “Combined presentation” is the most frequent clinical presentation.…”
Section: Discussionmentioning
confidence: 88%
“…Lamanna et al found intellectual disability to be a risk factor for ADHD. They found that 22% of the participants with ADHD had coexisting intellectual disability [43]. Fernell E. et al found that among adolescents diagnosed with ASD, 38% had intellectual disability [44].…”
Section: Discussionmentioning
confidence: 99%